APLIKASI EDIBLE COATING PATI SAGU DENGAN PENAMBAHAN EKSTRAK DAUN RANDU UNTUK MENINGKATKAN DAYA SIMPAN CABAI MERAH - Serliana, Afri; Efendi, Raswen; Johan, Vonny Setiaries (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
This research aims to study the application of randu leaves extract in edible coating of sago starch in order to maintain quality of red chilies during storage.  This study used a Completely Randomized Design (CRD) with 5 treatments and 3 replications, so that 15 (fifteen) experimental units were obtained.  The treatments used include P1 (without the addition of randu leaves extract), P2 (1% addition of randu leaves extract), P3 (3% addition of randu leaves extract), P4 (5% addition of randu leaves extract), and P5 (7 % addition of randu leaves extract).  The data obtained were statistically analyzed using Anova and DNMRT at 5% level.  The results showed that the addition of randu leaves extract significantly affected weight loss, hardness, vitamin C, total dissolved solids, and total microbes of red chili during storage.  The best treatment of this research was P5 which showed on red chilies after 15 days of storage that had 39,30% weight loss, 10,63 kgf/cm2hardness, 13,52 mg/100g vitamin C, 1,383°Brix total dissolved solids, and after 9 days of storage is 5,66 log CFU/g total microbes. Keywords: Edible coating, red chilies,randu leaves extracts.s